Prevalence of C‐shaped canal morphology using cone beam computed tomography – a systematic review with meta‐analysis. (11th July 2019) - Martins, J. N. R.; Marques, D.; Silva, E. J. N. L.; Caramês, J.; Mata, A.; Versiani, M. A.
Abstract: Background and aim: To perform a systematic review of anatomical studies using cone beam computed tomography (CBCT) to assess the influence of demographic factors (age, gender and geographic region) on the prevalence of C‐shaped canal anatomy in maxillary molars, mandibular premolars and molars. Data sources: A search was conducted between May and August 2018 in four electronic databases and five peer‐reviewed journals. The authors of included articles were also contacted for additional studies and the bibliographic references hand‐searched. Study eligibility criteria, participants and interventions: The research protocol was previously registered in the International Prospective Register of Ongoing Systematic Reviews (CRD42018095201) and included defined inclusion/exclusion criteria. Prevalence studies on C‐shaped canal anatomy in maxillary molars, mandibular premolars and molars were searched. Study appraisal and synthesis methods: The selected studies were submitted to full‐text analysis and critical appraisal by two evaluators using the Joanna Briggs Institute Critical Appraisal tool. The final group of papers ( n  = 25) were pooled and forest plots with proportions and odds ratio with a 95% confidence interval performed. Meta‐regression was undertaken to evaluate possible sources of heterogeneity and funnel plot visual analysis to assess publication bias. Results: The included studies reported data on 25 445 teeth of 13 142 patients. A significant difference in the average prevalence proportion of C‐shaped configuration was observed between mandibular first (0.3%; 0.1–0.6%) and second (12%; 10.3–13.7%) molars ( P  < 0.05). No significant difference in the prevalence of C‐shaped configurations was observed comparing males (13.5%; 8.8–18.3%) and females (20.5%; 13.7–27.4%) in mandibular second molars ( P  > 0.05), although males were associated with significantly lower odds (0.573; 0.511–0.641) ( P  < 0.05). The pooled proportion of C‐shaped anatomy in mandibular second molars in East Asian countries (39.6%; 36.0–43.1%) was significantly higher compared with other regions. Limitations: Because of the limited number of studies, no statistical analysis was performed for maxillary molars and mandibular premolars. Conclusion: Meta‐analysis revealed that gender and geographic region may act as a confounding factor for the prevalence of C‐shaped anatomy in mandibular second molars, whilst age did not influence the prevalence of C‐shaped configurations in this tooth group. Knowing these preoperative factors would help to anticipate complex morphologies in clinics.